Analysis of the impact of online education using EEG signals and machine learning algorithms - Hoque, Ehsanul; Ahmed, Tausif; Shabab, Mohammad Adituzzaman; Bakhtier, Tahsin Mohammad; Abdullah, Sayeem Md (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.